Closed–loop oxygen control improves oxygenation in pediatric patients under high–flow nasal oxygen—A randomized crossover study - Sandal, Ozlem; Ceylan, Gokhan; Topal, Sevgi; Hepduman, Pinar; Colak, Mustafa; Novotni, Dominik; Soydan, Ekin; Karaarslan, Utku; Atakul, Gulhan; Schultz, Marcus J.; Ağın, Hasan (Frontiers in Medicine, 2022)
Background We assessed the effect of a closed–loop oxygen control system in paediatric patients receiving high–flow nasal oxygen therapy (HFNO). Methods Multicentre, single–blinded, randomised, cross–over study. Patients aged between 1 month and 18 years of age receiving HFNO for acute hypoxemic respiratory failure (AHRF) were randomly assigned to start with a 2–hour period of closed–loop oxygen control or a 2–hour period of manual oxygen titrations, after which the patient switched to the alternative therapy. The endpoints were the percentage of time spent in predefined SpO2 ranges (primary), FiO2, SpO2/FiO2, and the number of manual adjustments. Findings We included 23 patients, aged median 18 (3–26) months. Patients spent more time in a predefined optimal SpO2 range when the closed–loop oxygen controller was activated compared to manual oxygen titrations (91·3% [IQR 78·4–95·1%] vs 63·0% [IQR 44·4–70·7%]), mean difference 28·2% [95%–CI 20·6–37·8%]; P<0.001). Median FiO2 was lower (33·3% [IQR 26·6–44·6%] vs 42·6% [IQR 33·6–49·9%]; P=0.07) but median SpO2/FiO2 was higher (289 [IQR 207–348] vs 194 [IQR 98–317]; P=0.023) with closed–loop oxygen control. The median number of manual adjustments was lower with closed–loop oxygen control (0·0 [IQR 0·0–0·0] vs 0·5 [IQR 0·0–1·0]; P<0.001). Conclusion Closed–loop oxygen control improves oxygenation therapy in paediatric patients receiving HFNO for AHRF, and potentially leads to more efficient oxygen use. It reduces the number of manual adjustments, which may translate in decreased workloads of healthcare providers.